Health-related quality of life in adults with congenital unilateral upper limb deficiency in Norway. A cross-sectional study. Issue 23 (5th November 2016) - Johansen, Heidi; Østlie, Kristin; Andersen, Liv Øinæs; Rand-Hendriksen, Svend
Abstract: Purpose: To examine subjective health-related quality of life (HRQoL) in adults with congenital unilateral upper limb deficiency (UULD) in Norway and to explore the associations between demographic and clinical factors and HRQoL. Method: Cross-sectional study comparing HRQoL, measured by SF-36, among adults with UULD and an age- and gender-matched control group from the Norwegian general population (NGP). Results: Seventy-seven respondents, median age 42 years (range: 20–82); 71% were women. Most had left-sided (61%), below elbow (53%), transverse (73%) deficiency. Compared to the NGP, the UULD group reported reduced HRQoL on all SF-36 subscales except for the role emotional (RE) scale ( p =0.321), mental health (MH) ( p =0.055) and mental component summary (MCS) ( p =0.064). The greatest difference was on the bodily pain (BP) scale (point difference of 20.0). Multiple linear regression models showed significant association between several physical- and mental SF-36 subscales and occupational status, occurrence of comorbidity and chronic pain. Conclusions: Persons with UULD reported reduced HRQoL on most SF-36 subscales, mostly in the physical health domain. Employment status, occurrence of comorbidity and chronic pain seem to have a negative impact on the HRQoL. Measures that can reduce pain and loss of function should be given particular attention in UULD rehabilitation. Implications for Rehabilitation: Persons with congenital unilateral upper limb deficiency (UULD) who experience pain and discomfort should seek professional help for evaluating their everyday coping strategies. Professionals who meet persons with UULD should examine anomalies, comorbidity, pain and employment status before choosing advices and actions. Individually adapted grip-improving devices, environments, physical exercise and pain management programs should be implemented early to reduce pain, loss of function and decreased HRQoL. A multidisciplinary approach is often necessary when counseling persons with UULD.